Efficacy of foot-and-mouth disease vaccination in goats and movement patterns of livestock amongst smallholder farmers in Mnisi, Bushbuckridge, South Africa - Fosgate, Geoffrey Theodore (University of Pretoria, 2020)
Thesis (PhD (Veterinary Science))-University of Pretoria, 2020.